Implementing the Green Economy: Avoiding the Middle Income Trap - Rismayanti Rismayanti (Universitas Gorontalo, 2023)
stract The purpose of this essay is to outline methods for implementing a green economy in Palopo City in order to escape the middle income trap. Since the creation of Palopo City in 2002, the per capita income of the residents of that city has fallen into the middle income range. The worst effect of this would be a lack of investor confidence in Palopo City, which could eventually lead to an increase in the poverty rate due to a lack of jobs. Therefore, Palopo City needs a plan to use the idea of a green economy to escape the middle class trap. The research design for this study is descriptive qualitative, and the methods for gathering data used are recording, interviews, and observation. The research results obtained are that currently the Palopo City government is building a city with the Business Traveler concept, but in this development, it is considered less than optimal, especially in the application of the green economy concept which has an impact on the accumulation of waste from business activities that pollutes the environment. Additionally, Palopo City's open unemployment rate is the second-highest in the country after Makassar City, necessitating increased job growth in the green economy industry. Strategies that can be applied in Palopo City to overcome the problem of the middle income trap by applying the green economy concept are: (1) waste management and circular economy, (2) application of extended producer responsibility policies as the role of producers who are ecologically literate, and (3) training programs green economy to prepare the human resources of Palopo City towards environmental-based economic development.